A randomized-controlled phase 2 study of the MET antibody emibetuzumab in combination with erlotinib as first-line treatment for EGFR mutation-positive NSCLC patients - Scagliotti, Giorgio V.; Moro-Sibilot, Denis; Kollmeier, Jens; Favaretto, Adolfo; Cho, Eun Kyung; Grosch, Heidrun; Kimmich, Martin; Girard, Nicolas; Tsai, Chun-Ming; Hsia, Te-Chun; Brighenti, Matteo; Schumann, Christian; et al. (Journal of thoracic oncology, 2020)
The hepatocyte growth factor receptor mesenchymal-epithelial transition (MET) is reported to be a negative prognostic marker in EGFR-mutant NSCLC and involved in resistance to EGFR inhibitors. Emibetuzumab, a humanized immunoglobulin G4 monoclonal bivalent MET antibody, blocks ligand-dependent and ligand-independent hepatocyte growth factor/MET signaling. This phase 2 study compared erlotinib with and without emibetuzumab in first-line treatment of EGFR-mutant metastatic NSCLC.
Available online - 14 October 2019
Gesehen am 11.03.2020